2019
DOI: 10.1175/jcli-d-18-0796.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Simulated by the Seoul National University Atmosphere Model Version 0 with a Unified Convection Scheme (SAM0-UNICON)

Abstract: As a contribution to phase 6 of the Coupled Model Intercomparison Project (CMIP6), the global climate simulated by an atmospheric general circulation model (GCM), the Seoul National University Atmosphere Model version 0 with a Unified Convection Scheme (SAM0-UNICON), is compared with observation and climates simulated by the Community Atmosphere Model version 5 (CAM5) and Community Earth System Model version 1 (CESM1), on which SAM0-UNICON is based. Both SAM0-UNICON and CESM1 successfully reproduce observed gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 42 publications
3
63
0
Order By: Relevance
“…SAM0-UNICON is one of the international GCMs participating in the CMIP6 and is based on the Community Atmosphere Model Version 5 (CAM5; [41,42]), but CAM5ʼs shallow ( [43]) and deep convection schemes ( [44]) were replaced by UNICON ( [45,46]) with a revised treatment of convective detrainment processes ( [47]). Reference [31] demonstrated that the global mean climate and ENSO simulated by SAM0/SEM0 are similar to those simulated by CAM5/CESM1. However, SAM0/SEM0 substantially improves the simulation of MJO, the diurnal cycle of precipitation, and TG.…”
Section: Data and Analysis Methodsmentioning
confidence: 79%
See 3 more Smart Citations
“…SAM0-UNICON is one of the international GCMs participating in the CMIP6 and is based on the Community Atmosphere Model Version 5 (CAM5; [41,42]), but CAM5ʼs shallow ( [43]) and deep convection schemes ( [44]) were replaced by UNICON ( [45,46]) with a revised treatment of convective detrainment processes ( [47]). Reference [31] demonstrated that the global mean climate and ENSO simulated by SAM0/SEM0 are similar to those simulated by CAM5/CESM1. However, SAM0/SEM0 substantially improves the simulation of MJO, the diurnal cycle of precipitation, and TG.…”
Section: Data and Analysis Methodsmentioning
confidence: 79%
“…Daily outgoing longwave radiation (OLR) and horizontal wind vector at levels of 850 and 200 hPa, which are used for defining MJO, came from observations of the Advanced Very-High-Resolution Radiometer satellite ( [36]) and the NCEP-NCAR reanalysis product ( [37]), respectively. In terms of GCMs, we conducted 400 years of coupled simulations at a 0.95°latitude×1.25°longitude horizontal resolution (nominally, 1°) in the pre-industrial period with the CESM1 and SEM0-UNICON ( [31]) driven by the forcing data obtained from phase six of the Coupled Model Intercomparison Project (CMIP6; [38]). Although not sufficient for reproducing the observed strength of TCs, 1°GCM simulations have been used in previous studies to examine the interannual and intraseasonal variations of the genesis of tropical cyclones ( [26,39,40]).…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed the analyses using monthly SST/SSH fields at 1° latitude × 1° longitude horizontal resolution in the tropics (25°S to 25°N). For the perfect model analysis, we use 450 years from the preindustrial period simulated by the Seoul National University Atmosphere Model Version 0 with a Unified Convection Scheme (SAM0‐UNICON; Park et al, ). All model analyses are tenfold cross validation of the 10 subsets of the simulation data: each subset consists of a 45 year evaluation period (10% of the entire data) and the remaining 405 year population.…”
Section: The Ma‐limmentioning
confidence: 99%